A low-cost single-crystal sodium-ion battery positive electrode active material, a preparation method therefor, and use thereof

CN118479490BActive Publication Date: 2026-10-16JIANGSU XIANGYING NEW ENERGY TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310102058.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-13
Publication Date
2026-10-16
Estimated Expiration
2043-02-13

AI Technical Summary

Technical Problem

[0003]目前氧化物体系钠离子电池正极活性物质主要为二次球形颗粒结构,但是传统的二次球形颗粒结构还存在如下一些问题:1、颗粒结构机械强度差,压实极片过程中,容易导致二次球破碎,影响极片压实密度和循环性能;2、活性材料与电解液接触表面积大,与电解液接触导致副反应增多,影响循环性能和安全性能

Benefits of technology

[0044]This invention uses magnesium to replace a portion of the metal elements, achieving a stable O3-type crystal structure in the oxide cathode active material. When this active material is used in sodium-ion batteries, the battery's specific capacity is improved, irreversible ion migration during charge and discharge is effectively suppressed, stabilizing the material's cycle performance. Simultaneously, production costs are significantly reduced. In other words, adding magnesium not only reduces costs but also improves the electrical performance of the sodium-ion battery. Furthermore, adding magnesium suppresses the irreversible migration of iron, enabling the material to achieve higher specific capacity at a lower cost while maintaining the cycle performance of the sodium-ion battery cathode material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118479490B_ABST
    Figure CN118479490B_ABST
Patent Text Reader

Abstract

The application discloses a low-cost single-crystal sodium-ion battery positive electrode active material and a preparation method and application thereof. i M x B y Mg z O2, wherein M is selected from a plurality of metal elements, 0.60<=i<=1.40, 0.6<=x<=0.9999, 0.0001<=y<=0.4, 0.0001<=z<=0.4, 0.9<=x+y+z<=1.1; the preparation method comprises the steps that a compound containing the metal element M, a magnesium source, a compound containing the boron element and a sodium source are added with water to form a slurry and are sand-milled to obtain a mixed slurry, and the mixed slurry is spray-dried and sintered to obtain the single-crystal sodium-ion battery positive electrode active material. The preparation method can improve the electrical performance of the positive electrode active material and reduce the cost of the positive electrode active material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of sodium-ion batteries, specifically relating to a low-cost monocrystalline sodium-ion battery positive electrode active material, its preparation method, and its applications. Background Technology

[0002] Due to the large radius of sodium ions, the selection of cathode active materials for sodium-ion batteries is relatively limited. Currently, the cathode active materials for sodium-ion batteries that have shown potential application prospects include three types of systems: Prussian blue, layered oxides, and polyanionic compounds. Among them, the O3 phase structure layered oxide system, similar to the ternary cathode active materials in lithium-ion batteries, has advantages such as high capacity and high compaction density, and is considered the most promising cathode material, adopted by sodium-ion battery companies both domestically and internationally.

[0003] Currently, the active material of the positive electrode in oxide-based sodium-ion batteries is mainly a secondary spherical particle structure. However, the traditional secondary spherical particle structure still has the following problems: 1. The particle structure has poor mechanical strength, which can easily lead to the breakage of the secondary spheres during the compaction of the electrode sheet, affecting the compaction density and cycle performance of the electrode sheet; 2. The active material has a large contact surface area with the electrolyte, which leads to an increase in side reactions and affects cycle performance and safety performance.

[0004] Furthermore, cost control of sodium-ion batteries is challenging. Achieving low-cost production of sodium-ion batteries is a key factor affecting their large-scale deployment. To replace lead-acid batteries on a large scale, the cost of sodium-ion batteries needs to be controlled below 0.5 yuan / Wh. This translates to a cost of ≤50,000 yuan / ton for the cathode material, ≤30,000 yuan / ton for the electrolyte, and ≤30,000 yuan / ton for the anode material. The cathode material primarily uses sodium nickel iron manganese oxide as its base material, and a nickel content generally ≥12wt% is required to meet the combined requirements for specific capacity and cycle life. Among the main elements, nickel costs about 220,000 yuan / ton, iron about 5,000 yuan / ton, manganese about 15,000 yuan / ton, and sodium carbonate about 5,000 yuan / ton. Nickel accounts for about 70% of the raw material cost of the cathode material. In order to meet the price requirements, the nickel content of sodium-ion battery cathode materials containing nickel must be reduced to ≤10wt%. However, this often affects the electrical performance of sodium-ion batteries and makes it difficult to meet the basic requirement of half-cell specific capacity ≥125mAh / g under 2.0-4.0V / 0.1C conditions.

[0005] Preparing the oxide system sodium-ion battery cathode active material into a single crystal morphology can significantly improve the disadvantages caused by the aforementioned secondary spherical particle structure. However, how to control the composition of the sodium-ion battery cathode active material and what preparation process can be used to synthesize a more perfect single crystal morphology have always been technical challenges in this field. Summary of the Invention

[0006] The purpose of this invention is to address the shortcomings and deficiencies of existing technologies by providing a method for preparing a single-crystal sodium-ion battery positive electrode active material. This method can prepare single-crystal sodium-ion battery positive electrode active material in a low-cost, large-scale, and stable manner. This positive electrode active material has a high compaction density and a small specific surface area, and exhibits excellent electrochemical performance, especially cycle performance, when used in sodium-ion batteries.

[0007] To solve the above technical problems, the present invention adopts the following technical solution:

[0008] A method for preparing a low-cost monocrystalline sodium-ion battery positive electrode active material, wherein the chemical formula of the monocrystalline sodium-ion battery positive electrode active material is Na. i M x B y Mg z O2, wherein M is selected from one or more combinations of Li, Al, Si, K, Ca, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Sr, Y, Zr, Nb, Mo, Ru, In, Sn, Sb, W, Ta, Ba, Bi, La, Ce, and Eu, with 0.60≤i≤1.40, 0.6≤x≤0.9999, 0.0001≤y≤0.4, 0.0001≤z≤0.4, and 0.9≤x+y+z≤1.1; the preparation method includes the steps of adding water to a compound containing the metal element M, a magnesium source, a compound containing the boron element, and a sodium source to form a slurry and milling it to obtain a mixed slurry, and the steps of spray drying the mixed slurry and sintering it to obtain the single-crystal sodium-ion battery positive electrode active material.

[0009] In some specific embodiments of the present invention, the chemical formula Na i M x B y Mg z In O2, 0.95≤i≤1.05, 0.8≤x≤0.9999, 0.0001≤y≤0.2, and 0.0001≤z≤0.2.

[0010] More preferably, the chemical formula Na i M x B y Mg z In O2, 0.98≤i≤1.04, 0.9≤x≤0.9999, 0.0001≤y≤0.1, and 0.01≤z≤0.15.

[0011] In some specific embodiments of the present invention, M is selected from one or more combinations of Fe, Ni, Mn, Cu, Ti, Zn, Ca, and Al.

[0012] In some specific embodiments of the present invention, the compound containing element M is selected from one or more combinations of oxides, hydroxides, carbonates, oxalates, and nitrates of element M.

[0013] Furthermore, the compound containing element M is selected from one or more combinations of nickel manganese hydroxide, ferric oxide, titanium dioxide, nickel oxide, manganese dioxide, zinc oxide, zinc carbonate, calcium oxide, calcium hydroxide, calcium carbonate, aluminum hydroxide, and aluminum oxide.

[0014] In some specific embodiments of the present invention, the boron-containing compound is selected from one or more combinations of boron oxide, boric acid, borates, borohydrides, boron trihalides, trifluoroboric acid, borate esters, boranes, and metal borides.

[0015] Furthermore, the boron-containing compound is selected from boric acid and boron oxide, or a combination of both.

[0016] In some specific embodiments of the present invention, the magnesium source is selected from one or more combinations of magnesium oxide, magnesium carbonate, magnesium hydroxide, magnesium nitrate, magnesium acetate, and magnesium citrate.

[0017] Furthermore, the magnesium source is selected from one or a combination of two of magnesium oxide, magnesium carbonate, and magnesium hydroxide.

[0018] In some specific embodiments of the present invention, the sodium source is selected from one or more combinations of sodium carbonate, sodium bicarbonate, sodium hydroxide, sodium oxide, sodium peroxide, sodium nitrate, sodium acetate, and sodium oxalate.

[0019] Furthermore, the sodium source is selected from one or more combinations of sodium carbonate, sodium bicarbonate, and sodium hydroxide.

[0020] In some specific embodiments of the present invention, the molar ratio of the compound containing element M, the compound containing element boron, the magnesium source, and the sodium source is (0.6-0.9999):(0.0001-0.4):(0.0001-0.4):(0.60-1.40).

[0021] More preferably, the molar ratio of the compound containing element M, the compound containing element boron, the magnesium source, and the sodium source is (0.6-0.9):(0.0001-0.1):(0.05-0.2):(0.90-1.10).

[0022] Further, the molar ratio of the compound containing element M, the compound containing element boron, the magnesium source, and the sodium source is (0.8-0.9):(0.01-0.06):(0.1-0.2):(0.95-1.05).

[0023] In some specific embodiments of the present invention, the grinding time is 0.6 to 7.8 hours.

[0024] Furthermore, the grinding time is 1 to 4 hours.

[0025] In some specific embodiments of the present invention, the grinding media of the sand mill is zirconia balls with a particle size of 0.1 to 0.8 mm.

[0026] In some specific embodiments of the present invention, the grinding speed is 800 to 3000 rpm.

[0027] Furthermore, the grinding speed is 1500–2500 rpm.

[0028] In some specific embodiments of the present invention, the solid content of the mixed slurry is 10% to 60%.

[0029] Furthermore, the solid content of the mixed slurry is 20-40%.

[0030] In some specific embodiments of the present invention, the median particle size of the particles in the mixed slurry is 20–800 nm.

[0031] In some specific embodiments of the present invention, the mixed slurry is pulverized after sintering.

[0032] Furthermore, during the spray drying process, the atomizing disc rotates at 1000–3000 rpm, the inlet air temperature is 150–300°C, and the outlet air temperature is 80–120°C.

[0033] In some specific embodiments of the present invention, the sintering is carried out in air at a temperature of 750–1100°C for a time of 5–25 hours.

[0034] Furthermore, the sintering temperature is 850–1000°C, and the time is 8–16 hours.

[0035] This invention discovers that by replacing a portion of the metal elements with magnesium, a stable O3-type crystal structure can be achieved in the oxide positive electrode active material. When this positive electrode active material is used in sodium-ion batteries, the specific capacity of the battery is improved, irreversible ion migration during charging and discharging is effectively suppressed, the cycle performance of the material is stabilized, and the production cost is significantly reduced. In other words, adding magnesium can reduce costs without affecting the electrical performance of sodium-ion batteries; on the contrary, it can improve the electrical performance of the batteries.

[0036] Secondly, by adding boron-containing compounds to the raw materials, the nanoscale primary particles rapidly fuse and coalesce during high-temperature sintering, resulting in monocrystalline sodium-ion battery positive electrode active materials of approximately 1-30 micrometers in size. This material is not in a loose state, thus possessing high compaction density, which can significantly reduce side reactions between the positive electrode material and the electrolyte. Furthermore, by controlling the boron content in the monocrystalline positive electrode active material, the particle size of the monocrystalline particles can be controlled.

[0037] Furthermore, in the preparation method of this invention, sand milling is used when preparing the mixed slurry. This can process water-soluble substances, achieving uniform mixing at the molecular level; it can also process water-insoluble raw materials, achieving uniform mixing between insoluble substances at the nanoscale; and it can also process uniform mixing between water-soluble and water-insoluble raw materials at the nanoscale. Sand milling ensures uniform mixing of raw materials at the nanoscale, and can stably obtain a cathode material with excellent electrochemical activity during high-temperature sintering. The sand milling method, the addition of a boron-containing compound, and the addition of a magnesium source used in this invention have a synergistic effect. All three are indispensable for preparing a low-cost single-crystal cathode active material with excellent cycle performance.

[0038] Finally, the present invention can also spray dry the mixed slurry. The spray drying method can maintain the uniform distribution of various raw materials in the uniformly mixed slurry during the drying process, and ensure that the various raw materials do not segregate during the molding process.

[0039] This invention further provides a single-crystal sodium-ion battery positive electrode active material prepared by the aforementioned method. This positive electrode active material has low cost and excellent electrical performance.

[0040] Furthermore, the microstructure of the positive electrode active material of the monocrystalline sodium-ion battery exhibits a monocrystalline structure, with an average particle size D. 50 Its size is 1-30 micrometers, and its compacted density is 2.8-3.6 g / cm³. 3 Its specific surface area is 0.3–1.0 m². 2 / g.

[0041] The present invention further provides the use of the aforementioned monocrystalline sodium-ion battery positive electrode active material in the positive electrode of a sodium-ion battery.

[0042] When this low-cost monocrystalline sodium-ion battery positive electrode active material is applied to the positive electrode of a sodium-ion battery, the resulting sodium-ion battery has a coin capacity of 125-140 mAh / g at 2.0-4.0V / 0.1C and 25℃, and retains more than 90% of the cylindrical battery's 100-cycle cycle rate at 25℃.

[0043] Compared with the prior art, the present invention has the following technical advantages:

[0044] This invention uses magnesium to replace a portion of the metal elements, achieving a stable O3-type crystal structure in the oxide cathode active material. When this active material is used in sodium-ion batteries, the battery's specific capacity is improved, irreversible ion migration during charge and discharge is effectively suppressed, stabilizing the material's cycle performance. Simultaneously, production costs are significantly reduced. In other words, adding magnesium not only reduces costs but also improves the electrical performance of the sodium-ion battery. Furthermore, adding magnesium suppresses the irreversible migration of iron, enabling the material to achieve higher specific capacity at a lower cost while maintaining the cycle performance of the sodium-ion battery cathode material.

[0045] The preparation method of the present invention can efficiently achieve uniform mixing of multiple raw materials at the nanoscale, and the mixed slurry can form a perfect layered O3 phase structure after sintering.

[0046] By doping boron with the sand milling method, large single crystals can be prepared, overcoming the shortcomings of existing technologies where the raw material particles are too fine, the sintered material is very loose with a large specific surface area, the compaction density of the positive electrode active material is low when making the electrode, and there are many side reactions and gas production between the positive electrode material and the electrolyte during battery cycling, resulting in poor battery cycle performance and safety performance.

[0047] This invention enables the preparation of 1-30 micrometer-sized single-crystal particles by controlling the boron content in the single-crystal positive electrode active material. These particles have stable surface properties and few side reactions with the electrolyte. By controlling the magnesium content in the positive electrode active material, when used in sodium-ion batteries, they can still exhibit good cycle performance while ensuring a high specific capacity. Attached Figure Description

[0048] Figure 1 NaNi prepared in Example 1 0.14 Fe 0.35 Mn 0.37 Zn 0.05 B 0.02 Mg 0.07 Scanning electron microscope image of O2;

[0049] Figure 2 NaNi prepared in Example 1 0.14 Fe 0.35 Mn 0.37 Zn 0.05 B 0.02 Mg 0.07 XRD pattern of O2;

[0050] Figure 3 NaNi prepared in Example 1 0.14 Fe 0.35 Mn0.37 Zn 0.05 B 0.02 Mg 0.07 The charge-discharge curve of O2.

[0051] Figure 4 NaNi prepared in Example 1 0.14 Fe 0.35 Mn 0.37 Zn 0.05 B 0.02 Mg 0.07 The full electrical cycle diagram of O2.

[0052] Figure 5 NaNi prepared in Example 2 0.14 Fe 0.40 Mn 0.37 B 0.02 Mg 0.07 Scanning electron microscope image of O2;

[0053] Figure 6 NaNi prepared in Example 2 0.14 Fe 0.40 Mn 0.37 B 0.02 Mg 0.07 XRD pattern of O2;

[0054] Figure 7 NaNi prepared in Example 2 0.14 Fe 0.40 Mn 0.37 B 0.02 Mg 0.07 The charge-discharge curve of O2.

[0055] Figure 8 NaNi prepared in Example 5 0.17 Fe 0.37 Mn 0.33 B 0.02 Mg 0.11 Scanning electron microscope image of O2;

[0056] Figure 9 NaNi prepared in Example 5 0.17 Fe 0.37 Mn 0.33 B 0.02 Mg 0.11 XRD pattern of O2;

[0057] Figure 10 NaNi prepared in Example 5 0.17 Fe 0.37 Mn 0.33 B 0.02 Mg 0.11The charge-discharge curve of O2.

[0058] Figure 11 NaNi prepared in Example 5 0.17 Fe 0.37 Mn 0.33 B 0.02 Mg 0.11 The full electrical cycle diagram of O2.

[0059] Figure 12 NaNi prepared in Example 6 0.16 Fe 0.40 Mn 0.34 B 0.02 Mg 0.08 Scanning electron microscope image of O2;

[0060] Figure 13 NaNi prepared in Example 6 0.16 Fe 0.40 Mn 0.34 B 0.02 Mg 0.08 XRD pattern of O2;

[0061] Figure 14 NaNi prepared in Example 6 0.16 Fe 0.40 Mn 0.34 B 0.02 Mg 0.08 The charge-discharge curve of O2.

[0062] Figure 15 NaNi prepared for Comparative Example 1 1 / 3 Fe 1 / 3 Mn 1 / 3 Scanning electron microscope image of O2;

[0063] Figure 16 NaNi prepared for Comparative Example 1 1 / 3 Fe 1 / 3 Mn 1 / 3 XRD pattern of O2;

[0064] Figure 17 NaNi prepared in Comparative Example 1 1 / 3 Fe 1 / 3 Mn 1 / 3 The charge-discharge curve of O2.

[0065] Figure 18 NaNi prepared for Comparative Example 2 0.17 Fe 0.37 Mn 0.34 Mg 0.12 Scanning electron microscope image of O2;

[0066] Figure 19 NaNi prepared for Comparative Example 2 0.17 Fe 0.37 Mn 0.34 Mg 0.12 XRD pattern of O2;

[0067] Figure 20 NaNi prepared for Comparative Example 2 0.17 Fe 0.37 Mn 0.34 Mg 0.12 The charge-discharge curve of O2.

[0068] Figure 21 NaNi prepared for Comparative Example 2 0.17 Fe 0.37 Mn 0.34 Mg 0.12 The full electrical cycle diagram of O2. Detailed Implementation

[0069] To better understand the content of this invention, further description is provided below with reference to specific embodiments and accompanying drawings. It should be understood that these embodiments are only for further illustration of the invention and are not intended to limit the scope of the invention. Furthermore, it should be understood that after reading the content of this invention, any improvements and adjustments made to this invention by those skilled in the art without departing from the principles of the invention are still within the protection scope of this invention. Unless otherwise specified, all raw materials described below are commercially available.

[0070] In the following examples and comparative examples, half-cell charge-discharge curve tests were conducted: First, a sodium-ion half-cell was prepared: 20g of the prepared positive electrode active material was weighed, and 0.64g of conductive agent SP and 0.64g of PVDF dissolved in NMP were added. After mixing evenly, the mixture was coated onto aluminum foil to form an electrode sheet. In a glove box under an argon atmosphere, a button cell was assembled using a sodium metal sheet as the negative electrode, Celgard 2700 as the separator, and 1mol / L NaPF6+EC:DEC(1:1)+5%FEC as the electrolyte. Then, the charge-discharge curves were tested at a voltage range of 2.0-4.0V, a charge-discharge rate of 0.1C, and a test temperature of 25±2℃.

[0071] Cyclic performance testing was conducted using cylindrical batteries: First, cylindrical 18650 sodium-ion batteries were prepared: A cathode slurry was mixed according to the ratio of sodium cathode: SP: CNT: PVDF = 95.5:1.7:0.8:2.0, and coated under conditions of relative humidity ≤15%, achieving a double-sided areal density of 370 g / m³. 2After being rolled to a compaction density of 3.05 g / cm³, it was matched with a 16 μm PP / PE separator and a hard carbon negative electrode sheet, wound, and placed into a casing. In an argon-atmospheric glove box, using 1 mol / L NaPF6 + EC:DEC (1:1) + 5% FEC as the electrolyte, an 18650 battery was assembled. Cycling performance was tested for 100 cycles at 25°C within a voltage range of 2.0–3.9 V and a charge / discharge rate of 1C.

[0072] Example 1

[0073] This embodiment provides a sodium-ion battery positive electrode active material with the chemical formula NaNi. 0.14 Fe 0.35 Mn 0.37 Zn 0.05 B 0.02 Mg 0.07 O2 (Ni content ~7.59wt%), the preparation method includes the following steps:

[0074] (1) Take 0.7 mol NiO, 0.875 mol Fe2O3, 1.85 mol MnO2, 0.25 mol ZnO, 0.1 mol H3BO3, 0.35 mol MgO, and 2.5 mol Na2CO3, and add all raw materials to 3.5 L of water to make a slurry.

[0075] (2) Add the slurry obtained in step (1) to a sand mill and grind for 3 hours. The grinding media are zirconia balls with a particle size of 0.2 mm. The sand milling speed is 2500 rpm. Grind to obtain a mixed slurry with an average particle size of about 350 nm.

[0076] (3) The mixed slurry obtained in step (2) is transferred into a mixing tank and stirred thoroughly. Pure water is added to adjust the slurry to a solid content of 30±1%. The slurry is spray-dried under the conditions of atomization frequency of 35Hz, air inlet temperature of 190℃ and air outlet temperature of 85℃ in a spray drying equipment. After drying, the product is sintered in an air atmosphere furnace at 850~1000℃ for 12 hours, cooled to below 80℃, crushed by jaw crusher, roller crusher and pulverizer to obtain sodium-ion battery positive electrode active material, sample name NFMZ-BM1.

[0077] Scanning electron microscope image of NFMZ-BM1 as follows Figure 1 As shown, the material exhibits a single-crystal morphology. The XRD pattern of NFMZ-BM1 is shown below. Figure 2 As shown, this material exhibits a pure-phase layered structure of α-NaFeO2. The charge-discharge curves of NFMZ-BM1 are shown below. Figure 3 As shown, within a voltage window of 2.0–4.0V, the discharge specific capacity at a 0.1C rate is 130.0 mAh / g. The full-cycle diagram of NFMZ-BM1 is shown below. Figure 4 As shown, within a voltage window of 2.0–3.9V at 25℃ and a 1C rate, the capacity retention rate is 91.3% after 100 cycles.

[0078] Example 2

[0079] This embodiment provides a sodium-ion battery positive electrode active material with the chemical formula NaNi. 0.14 Fe 0.40 Mn 0.37 B 0.0 2Mg 0.07 O2 (Ni content ~7.62wt%), the preparation method includes the following steps:

[0080] (1) Take 0.7 mol NiO, 1.0 mol Fe2O3, 1.85 mol MnO2, 0.1 mol H3BO3, 0.35 mol MgO, and 2.5 mol Na2CO3, and add all raw materials to 3.5 L of water to make a slurry;

[0081] (2) Add the slurry obtained in step (1) to a sand mill and grind for 3 hours. The grinding media are zirconia balls with a particle size of 0.2 mm. The sand milling speed is 2500 rpm. Grind to obtain a mixed slurry with an average particle size of about 350 nm.

[0082] (3) The mixed slurry obtained in step (2) is transferred into a mixing tank and stirred thoroughly. Pure water is added to adjust the slurry to a solid content of 30±1%. The slurry is spray-dried under the conditions of atomization frequency of 35Hz, air inlet temperature of 190℃ and air outlet temperature of 85℃ in a spray drying equipment. After drying, the product is sintered in an air atmosphere furnace at 850~1000℃ for 12 hours, cooled to below 80℃, crushed by jaw crusher, roller crusher and pulverizer to obtain sodium-ion battery positive electrode active material, sample name NFM-BM2.

[0083] Scanning electron microscope image of NFM-BM2 as follows Figure 5 As shown, the material exhibits a single-crystal morphology. The XRD pattern of NFM-BM2 is shown below. Figure 6 As shown, this material exhibits a pure-phase layered structure of α-NaFeO2. The charge-discharge curves of NFM-BM2 are shown below. Figure 7 As shown, within the voltage window of 2.0 to 4.0 V, the discharge specific capacity at a 0.1C rate is 126.4 mAh / g.

[0084] Example 3

[0085] This embodiment provides a sodium-ion battery positive electrode active material with the chemical formula NaNi. 0.17 Fe 0.34 Mn 0.37 Ti0.04 B 0.02 Mg 0.06 O2 (Ni content ~9.25wt%), the preparation method includes the following steps:

[0086] (1) Take 0.85 mol NiO, 0.85 mol Fe2O3, 1.85 mol MnO2, 0.2 mol TiO2, 0.1 mol H3BO3, 0.30 mol MgO, and 2.5 mol Na2CO3, and add all raw materials to 3.5 L of water to make a slurry;

[0087] (2) Add the slurry obtained in step (1) to a sand mill and grind for 3 hours. The grinding media are zirconia balls with a particle size of 0.2 mm. The sand milling speed is 2500 rpm. Grind to obtain a mixed slurry with an average particle size of about 350 nm.

[0088] (3) The mixed slurry obtained in step (2) is transferred into a mixing tank and stirred thoroughly. Pure water is added to adjust the slurry to a solid content of 30±1%. The slurry is spray-dried under the conditions of atomization frequency of 35Hz, air inlet temperature of 190℃ and air outlet temperature of 85℃ in a spray drying equipment. After drying, the product is sintered in an air atmosphere furnace at 850~1000℃ for 12 hours, cooled to below 80℃, crushed by jaw crusher, roller crusher and pulverizer to obtain sodium-ion battery positive electrode active material, sample name NFMT-BM3.

[0089] Example 4

[0090] This embodiment provides a sodium-ion battery positive electrode active material with the chemical formula NaNi. 0.17 Fe 0.33 Mn 0.33 B 0.0 2Mg 0.15 O2 (Ni content ~9.47wt%), the preparation method includes the following steps:

[0091] (1) Take 0.85 mol NiO, 0.825 mol Fe2O3, 1.65 mol MnO2, 0.1 mol H3BO3, 0.75 mol MgO, and 2.5 mol Na2CO3, and add all raw materials to 3.5 L of water to make a slurry.

[0092] (2) Add the slurry obtained in step (1) to a sand mill and grind for 3 hours. The grinding media are zirconia balls with a particle size of 0.2 mm. The sand milling speed is 2500 rpm. Grind to obtain a mixed slurry with an average particle size of about 350 nm.

[0093] (3) The mixed slurry obtained in step (2) is transferred into a mixing tank and stirred thoroughly. Pure water is added to adjust the slurry to a solid content of 30±1%. The slurry is spray-dried under the conditions of atomization frequency of 35Hz, air inlet temperature of 190℃ and air outlet temperature of 85℃ in a spray drying equipment. After drying, the product is sintered in an air atmosphere furnace at 850~1000℃ for 12 hours, cooled to below 80℃, crushed by jaw crusher, roller crusher and pulverizer to obtain sodium-ion battery positive electrode active material, sample name NFM-BM4.

[0094] Example 5

[0095] This embodiment provides a sodium-ion battery positive electrode active material with the chemical formula NaNi. 0.17 Fe 0.37 Mn 0.33 B 0.0 2Mg 0.11 O2 (Ni content ~9.36wt%), the preparation method includes the following steps:

[0096] (1) Take 0.85 mol NiO, 0.925 mol Fe2O3, 1.65 mol MnO2, 0.1 mol H3BO3, 0.55 mol MgO, and 2.5 mol Na2CO3 and add all raw materials to 3.5 L of water to make a slurry.

[0097] (2) Add the slurry obtained in step (1) to a sand mill and grind for 3 hours. The grinding media are zirconia balls with a particle size of 0.2 mm. The sand milling speed is 2500 rpm. Grind to obtain a mixed slurry with an average particle size of about 350 nm.

[0098] (3) The mixed slurry obtained in step (2) is transferred into a mixing tank and stirred thoroughly. Pure water is added to adjust the slurry to a solid content of 30±1%. The slurry is spray-dried under the conditions of atomization frequency of 35Hz, air inlet temperature of 190℃ and air outlet temperature of 85℃ in a spray drying equipment. After drying, the product is sintered in an air atmosphere furnace at 850~1000℃ for 12 hours, cooled to below 80℃, crushed by jaw crusher, roller crusher and pulverizer to obtain sodium-ion battery positive electrode active material, sample name NFM-BM5.

[0099] Scanning electron microscope image of NFM-BM5 as follows Figure 8 As shown, the material exhibits a single-crystal morphology. The XRD pattern of NFM-BM5 is shown below. Figure 9 As shown, this material exhibits a pure-phase layered structure of α-NaFeO2. The charge-discharge curves of NFM-BM5 are shown below. Figure 10 As shown, within a voltage window of 2.0–4.0V, the discharge specific capacity at a 0.1C rate is 138.8 mAh / g. The full-cycle diagram of NFM-BM5 is shown below. Figure 11As shown, within a voltage window of 2.0–3.9V at 25℃ and a 1C rate, the capacity retention rate is 98.91% after 100 cycles.

[0100] Example 6

[0101] This embodiment provides a sodium-ion battery positive electrode active material with the chemical formula NaNi. 0.16 Fe 0.40 Mn 0.34 B 0.0 2Mg 0.08 O2 (Ni content ~8.73wt%), the preparation method includes the following steps:

[0102] (1) Take 0.8 mol of NiO, 1.0 mol of Fe2O3, 1.7 mol of MnO2, 1.0 mol of H3BO3, 0.4 mol of MgO, and 2.5 mol of Na2CO3 and add all raw materials to 3.5 L of water to make a slurry.

[0103] (2) Add the slurry obtained in step (1) to a sand mill and grind for 3 hours. The grinding media are zirconia balls with a particle size of 0.2 mm. The sand milling speed is 2500 rpm. Grind to obtain a mixed slurry with an average particle size of about 350 nm.

[0104] (3) The mixed slurry obtained in step (2) is transferred into a mixing tank and stirred thoroughly. Pure water is added to adjust the slurry to a solid content of 30±1%. The slurry is spray-dried under the conditions of atomization frequency of 35Hz, air inlet temperature of 190℃ and air outlet temperature of 85℃ in a spray drying equipment. After drying, the product is sintered in an air atmosphere furnace at 850~1000℃ for 12 hours, cooled to below 80℃, crushed by jaw crusher, roller crusher and pulverizer to obtain sodium-ion battery positive electrode active material, sample name NFM-BM6.

[0105] Scanning electron microscope image of NFM-BM6 as follows Figure 12 As shown, the material exhibits a single-crystal morphology. The XRD pattern of NFM-BM6 is shown below. Figure 13 As shown, this material exhibits a pure-phase layered structure of α-NaFeO2. The charge-discharge curves of NFM-BM6 are shown below. Figure 14 As shown, within the voltage window of 2.0 to 4.0 V, the discharge specific capacity at a 0.1C rate is 134.8 mAh / g.

[0106] Comparative Example 1

[0107] This embodiment provides a sodium-ion battery positive electrode active material with the chemical formula NaNi. 1 / 3 Fe 1 / 3 Mn 1 / 3O2 (Ni content ~17.55wt%), the preparation method includes the following steps:

[0108] (1) Take 1.65 mol of NiO, 0.835 mol of Fe2O3, 1.65 mol of MnO2, and 2.5 mol of Na2CO3, and add all raw materials to 3.5 L of water to make a slurry;

[0109] (2) Add the slurry obtained in step (1) to a sand mill and grind for 3 hours. The grinding media are zirconia balls with a particle size of 0.2 mm. The sand milling speed is 2500 rpm. Grind to obtain a mixed slurry with an average particle size of about 350 nm.

[0110] (3) The mixed slurry obtained in step (2) is transferred into a mixing tank and stirred thoroughly. Pure water is added to adjust the slurry to a solid content of 30±1%. The slurry is spray-dried under the conditions of atomization frequency of 35Hz, air inlet temperature of 190℃ and air outlet temperature of 85℃ in a spray drying equipment. After drying, the product is sintered in an air atmosphere furnace at 850~1000℃ for 12 hours, cooled to below 80℃, crushed by jaw crusher, roller crusher and pulverizer to obtain sodium-ion battery positive electrode active material, sample name NFM-1.

[0111] Scanning electron microscope image of NFM-1 as follows Figure 15 As shown, the material appears to be a loose, secondary granular sphere, with primary particles within the spheres approximately 0.5 micrometers in size. The XRD pattern of NFM-1 is shown below. Figure 16 As shown, this material exhibits a pure-phase layered structure of α-NaFeO2. The charge-discharge curves of NFM-1 are shown below. Figure 17 As shown, within the voltage window of 2.0 to 4.0 V, the discharge specific capacity at a 0.1C rate is 125.0 mAh / g.

[0112] Comparative Example 2

[0113] This embodiment provides a sodium-ion battery positive electrode active material with the chemical formula NaNi. 0.17 Fe 0.37 Mn 0.34 Mg 0.12 O2 (Ni content ~9.31wt%), the preparation method includes the following steps:

[0114] (1) Take 0.85 mol of NiO, 0.925 mol of Fe2O3, 1.7 mol of MnO2, 0.6 mol of MgO, and 2.5 mol of Na2CO3, and add all raw materials to 3.5 L of water to make a slurry;

[0115] (2) Add the slurry obtained in step (1) to a sand mill and grind for 3 hours. The grinding media are zirconia balls with a particle size of 0.2 mm. The sand milling speed is 2500 rpm. Grind to obtain a mixed slurry with an average particle size of about 350 nm.

[0116] (3) The mixed slurry obtained in step (2) is transferred into a mixing tank and stirred thoroughly. Pure water is added to adjust the slurry to a solid content of 30±1%. The slurry is spray-dried under the conditions of atomization frequency of 35Hz, air inlet temperature of 190℃ and air outlet temperature of 85℃ in a spray drying equipment. After drying, the product is sintered in an air atmosphere furnace at 850~1000℃ for 12 hours, cooled to below 80℃, crushed by jaw crusher, roller crusher and pulverizer to obtain sodium-ion battery positive electrode active material, sample name NFM-M2.

[0117] Scanning electron microscope image of NFM-M2 as follows Figure 18 As shown, the material appears to be a loose, secondary granular sphere, with primary particles within the spheres approximately 0.5 micrometers in size. The XRD pattern of NFM-M2 is shown below. Figure 19 As shown, this material exhibits a pure-phase layered structure of α-NaFeO2. The charge-discharge curves of NFM-M3 are shown below. Figure 20 As shown, within a voltage window of 2.0–4.0V, the discharge specific capacity at a 0.1C rate is 138.7 mAh / g. The full-cycle diagram of NFM-M2 is shown below. Figure 21 As shown, within a voltage window of 2.0 to 3.9V at 25℃ and a 1C rate, the capacity retention rate is 85.78% after 100 cycles.

[0118] Performance testing

[0119] The physicochemical properties of the positive electrode active materials prepared in Examples 1-6 and Comparative Examples 1-2 were tested, and the results are shown in Table 1 below.

[0120] Table 1. Physical properties of positive electrode active materials

[0121]

[0122]

[0123] The positive electrode active materials prepared in Examples 1-6 and Comparative Examples 1-2 were used for sodium-ion battery performance testing, and the test results are shown in Table 2 below.

[0124] Table 2. Performance of Sodium-ion Batteries

[0125]

[0126] As shown in Tables 1-2 above, the present invention achieves a perfect layered single-crystal structure of positive electrode active material by adding water to form a mixed slurry during precursor grinding, spray drying before sintering, and adding boron-containing compounds and magnesium elements to the raw materials. The single crystal particles are large and densely grown, significantly increasing the compaction density of the positive electrode active material and reducing the specific surface area. When this positive electrode active material is used in sodium-ion batteries, it can significantly improve the cycle performance at high temperatures while ensuring a high specific capacity, and the cost of the positive electrode active material is significantly reduced.

[0127] The above embodiments are only for illustrating the technical concept and features of the present invention. Their purpose is to enable those skilled in the art to understand the content of the present invention and implement it accordingly. They should not be used to limit the scope of protection of the present invention. All equivalent changes or modifications made in accordance with the spirit and essence of the present invention should be covered within the scope of protection of the present invention.

Claims

1. A method for preparing a single-crystal sodium-ion battery positive electrode active material, characterized in that: The chemical formula of the positive electrode active material of the monocrystalline sodium-ion battery is Na. i M x B y Mg z O2, wherein M is selected from one or more combinations of Li, Al, Si, K, Ca, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Sr, Y, Zr, Nb, Mo, Ru, In, Sn, Sb, W, Ta, Ba, Bi, La, Ce, and Eu, with 0.60≤i≤1.40, 0.6≤x≤0.9999, 0.0001≤y≤0.4, 0.0001≤z≤0.4, and 0.9≤x+y+z≤1.1; the preparation method includes the steps of adding water to a compound containing the metal element M, a magnesium source, a compound containing the boron element, and a sodium source to form a slurry and milling it to obtain a mixed slurry, and the steps of spray drying the mixed slurry and sintering it to obtain the single-crystal sodium-ion battery positive electrode active material; The microstructure of the positive electrode active material of the monocrystalline sodium-ion battery is a monocrystalline structure. The boron-containing compound is selected from one or more combinations of boron oxide, boric acid, borates, borohydrides, boron trihalides, trifluoroboric acid, borate esters, boranes, and metal borides.

2. The preparation method according to claim 1, characterized in that: The chemical formula Na i M x B y Mg z In O2, 0.95≤i≤1.05, 0.8≤x≤0.9999, 0.0001≤y≤0.2, and 0.0001≤z≤0.

2.

3. The preparation method according to claim 1, characterized in that: The compound containing the metal element M is selected from one or more combinations of oxides, hydroxides, carbonates, oxalates, and nitrates of element M.

4. The preparation method according to claim 1, characterized in that: The sodium source is selected from one or more combinations of sodium carbonate, sodium bicarbonate, sodium hydroxide, sodium oxide, sodium peroxide, sodium nitrate, sodium acetate, and sodium oxalate.

5. The preparation method according to claim 1, characterized in that: The magnesium source is selected from one or more combinations of magnesium oxide, magnesium carbonate, magnesium hydroxide, magnesium nitrate, magnesium acetate, and magnesium citrate.

6. The preparation method according to claim 1, characterized in that: The molar ratio of the compound containing metal element M, the compound containing boron element, the magnesium source, and the sodium source is (0.6~0.9999): (0.0001~0.4): (0.0001~0.4): (0.60~1.40).

7. The preparation method according to claim 1, characterized in that: The grinding time is 0.6 to 7.8 hours; and / or the grinding media of the sand mill is zirconia balls with a particle size of 0.1 to 0.8 mm; and / or the grinding speed is 800 to 3000 rpm.

8. The preparation method according to claim 1, characterized in that: The solid content of the mixed slurry is 10% to 60%; and / or the median particle size of the particles in the mixed slurry is 20 to 800 nm.

9. The preparation method according to claim 1, characterized in that: During the spray drying process, the atomizing disc rotates at 1000~3000 rpm, the inlet air temperature is 150~300℃, and the outlet air temperature is 80~120℃.

10. The preparation method according to claim 1, characterized in that: The sintering is carried out in air at a temperature of 750-1100°C for 5-25 hours; and / or the mixed slurry is pulverized after sintering.

11. A single-crystal sodium-ion battery positive electrode active material prepared by the preparation method according to any one of claims 1 to 10.

12. The single-crystal sodium-ion battery positive electrode active material according to claim 11, characterized in that: The microstructure of the single-crystal sodium-ion battery positive electrode active material exhibits a single-crystal structure with an average particle size D. 50 Its micrometers range from 1 to 30 micrometers, and its compacted density is 2.8 to 3.6 g / cm³. 3 Its specific surface area is 0.3~1.0 m². 2 / g.

13. The use of the monocrystalline sodium-ion battery positive electrode active material according to claim 12 in the positive electrode of a sodium-ion battery.

Citation Information

Patent Citations

  • Monocrystalline sodium ion battery positive electrode material, preparation method thereof and battery

    CN115275178A

  • Positive electrode active material for sodium ion battery as well as preparation method and application of positive electrode active material

    CN115377394A